Autoimmune Pancreatitis Mouse Model. (21st February 2018) - Kamata, Ken; Watanabe, Tomohiro; Minaga, Kosuke; Strober, Warren; Kudo, Masatoshi
Abstract: Autoimmune pancreatitis (AIP) is a chronic fibro‐inflammatory disorder of the pancreas. However, extensive clinico‐pathological analyses have revealed that AIP is, in reality, a pancreatic manifestation of a newly described systemic disease known as IgG4‐related disease (IgG4‐RD). IgG4‐RD is characterized by enhanced local and systemic IgG4 antibody (Ab) responses as well as inflammation involving multiple organs, including the pancreas, bile ducts, and salivary glands. Although mice lack the IgG4 Ab subtype, autoimmune‐prone MRL/Mp mice treated with repeated injection with polyinosinic‐polycytidylic acid (poly (I:C)) provide an experimental model of AIP. These mice exhibit massive destruction of pancreatic architecture associated with pancreatic immune cell infiltration and fibrosis. Moreover, this experimental AIP may be accompanied by involvement of multiple organs as well as elevation of serum levels of autoAbs, resembling humans with IgG4‐RD. Thus, elucidation of the molecular mechanisms accounting for the development of experimental AIP can potentially provide new insights into the immuno‐pathogenesis of human IgG4‐related AIP. © 2018 by John Wiley & Sons, Inc.